Analisis Return Saham Perusahaan LQ 45 Tahun 2018 - Muchayatin Muchayatin (Serat Acitya, 2020)
Current ratio, Debt to Equity (DER) ratio, and Return On Assets (ROA) to the return of LQ 45 company shares in 2018 period. The population in this study are companies that incorporated in LQ 45 Index for the period 2018 of 45 companies, while the subject or unit of analysis in this study is the financial statements of the selected companies as populations.Determination of domestic shares to be allocated to countries with LQ-45 status in 2018 period and given regularly to the government. The Indonesia Stock Exchange also has appropriate price data, current ratios, debt to equity ratios and asset returns of 37 companies. The amount of data used is secondary data obtained by registration, while the data obtained is not obtained directly from the object purchased. The research data was obtained through IDX in 2018. While the data analysis technique used is multiple linear regression.The research results seen from multiple linear regression analysis showed that Return On Assets (ROA) has a positive and not significant effect on Stock Return. While Current Ratio (CR) and Debt on Equity Ratio (DER) have negative and significant effect on Stock Return.Keywords: Current Ratio (CR), Debt on Equity Ratio (DER), Return On Assets (ROA), Return stock.